PENERAPAN MEKANISME HAK JAWAB BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS DALAM TINDAK PIDANA PENCEMARAN NAMA BAIK - Dianto Simanjuntak; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Implementation Mechanism of Right of Reply by Act No. 40 of 1999 on the Press and the application of the Criminal Code (the Code of Penal Code) is an issue in dispute resolution press specifically the crime of defamation. On the one hand look when problems occur between the press and the public or the press with laws such as the police, the legal consequences that should be accepted by the press is going to deal with the articles of defamation in the book of the law of criminal law (Criminal Code). Jurisprudence on "Mechanisms right of reply" by the verdict of the Chief Justice of the Supreme Court composed of M. Yahya Harahap, SH (Chairman) by Judge H. Yahya, SH and Kohar Day Soemarmo, SH in case No. 3173.K / Pdt / 1991, on April 28, 1993 has stated that the Right of Reply mechanism is something that must be taken first before making a complaint to the court. However, the jurisprudence is not followed by another judge in dealing with cases of press, because Indonesia does not adhere to the principle of Presedent where the judge is bound by another judge, either equivalent or higher. Opinion of Judge divided, so there is a different issue: Is it supposed to use the right to reply and whether citizens are still justified in suing the press if a right of reply has been used and already served the press. And this is legal uncertainty in a dispute memngakibatkan press.The purpose of this Thesis Writing namely: first, to know Application Thread Rights Mechanism and Application of the Code of Penal (Penal Code) for dispute resolution press specifically the crime of defamation against press freedom in Indonesia. second, to determine the ideal of setting notch mechanism Right of Reply in criminal defamation committed by the press.This research is a normative legal research or can be also called the doctrinal legal research. From the research problem there are two main things that concluded, first, to strengthen the role and position of the Press Council as the regulatory mechanism of the right of reply so that the Right of Reply mechanism is the mechanism to be followed in the press specifically dispute the crime of defamation. Second, the judiciary Establishment of the press which supports freedom of the press according to the theory of social responsibility of the press.Keywords: Press-setting mechanism Right of Reply-System-Pollution-Name Good